2019
DOI: 10.1002/cncr.32289
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of ofatumumab and bendamustine versus ofatumumab, bendamustine, and bortezomib in previously untreated patients with high‐risk follicular lymphoma: CALGB 50904 (Alliance)

Abstract: BACKGROUND: This multicenter, randomized phase 2 trial evaluated complete responses (CRs), efficacy, and safety with ofatumumab and bendamustine and with ofatumumab, bendamustine, and bortezomib in patients with untreated, high-risk follicular lymphoma (FL). METHODS: Patients with grade 1 to 3a FL and either a Follicular Lymphoma International Prognostic Index (FLIPI) score of 2 with 1 lymph node >6 cm or an FLIPI score of 3 to 5 were randomized to arm A (ofatumumab, bendamustine, and maintenance ofatumumab) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Five randomized studies (CALGB50904, 10 E2408, 11 FOLL05, 12,13 GALLIUM, 14 RELEVANCE 15 ) were included; four included rituximab during induction treatment (Table S1). The GALLIUM trial was split into three subunits according to chemotherapy regimen (CHOP n = 200, CVP n = 47, bendamustine n = 323) which was chosen by each enrolling site, and the RELEVANCE trial was split into two subunits based on sex (male n = 196, female n = 190) because all patients in the experimental arm received the R‐lenalidomide regimen.…”
Section: Resultsmentioning
confidence: 99%
“…Five randomized studies (CALGB50904, 10 E2408, 11 FOLL05, 12,13 GALLIUM, 14 RELEVANCE 15 ) were included; four included rituximab during induction treatment (Table S1). The GALLIUM trial was split into three subunits according to chemotherapy regimen (CHOP n = 200, CVP n = 47, bendamustine n = 323) which was chosen by each enrolling site, and the RELEVANCE trial was split into two subunits based on sex (male n = 196, female n = 190) because all patients in the experimental arm received the R‐lenalidomide regimen.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, it makes a distinction between the two potential censoring reasons, namely LTFU and administrative censoring. While Korn's paper is regularly cited in the literature by papers which analyze RCTs, the citation is typically used to refer to time to censoring (see, e.g., Blum et al 21 ). We are not aware of an actual computation of 6 in a trial.…”
Section: Quantities Used In the Literature To Quantify “Follow‐up”mentioning
confidence: 99%
“…Quantity 6, Korn's potential follow-up time, 20 is a generalization of time to censoring (Quantity 3) and estimates the probability to be under follow-up at a given time t. To this end, it makes a distinction between the two potential censoring reasons, namely LTFU and administrative censoring. While Korn's paper is regularly cited in the literature by papers which analyze RCTs, the citation is typically used to refer to time to censoring (see, e.g., Blum et al 21 ). We are not aware of an actual computation of 6 in a trial.…”
Section: Quantities Used In the Literature To Quantify " Follow-up"mentioning
confidence: 99%
“…A 2015 phase II trial treated 49 indolent NHL patients with bendamustine and ofatumumab and found the ORR comparable to historical treatments with bendamustine and rituximab ( 98 ). A 2017 study by the Alliance found PFS was comparable between ofatumumab with bendamustine (OB) and historical rituximab with bendamustine in previously untreated FL, despite an initially improved CR with OB ( 99 ). Given conflicting reports of increased benefits, additional randomized phase III trials and more biologically representative in vitro assays are needed to fully assess the differences in efficacy between these CD20 mAbs.…”
Section: Shortfalls Of Rituximab and Alternativesmentioning
confidence: 99%